2016
DOI: 10.1016/j.jdiacomp.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in acute kidney injury of hospitalized adults with diabetes

Abstract: Objective To determine whether there is a racial difference in the risk of acute kidney injury between hospitalized black and white adults with diabetes mellitus in the United States Research Design and Methods We analyzed cross-sectional data from the 2000–2010 National Hospital Discharge Survey (NHDS) to compare the odds of AKI among hospitalized black and white adults with diabetes. After excluding records in which race status was missing, race was other than white or black, discharge status was not provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Previous studies have hypothesized that diabetic patients who develop AKI may possibly have reduced nephron mass and perhaps less severe associated nonrenal disease compared to those without diabetes, suggesting that a more milder form of in-jury was required to cause AKI in this group of patients [18]. Besides, in support of our findings, previous study has documented that diabetic patients have predominantly stage 1 AKI with fast recovery [28]. We therefore suspect the lower risk of in-hospital and post-hospitalization mortality associated with DM may be due to a lower severity of cardiovascular disease in the surviving population together with a less severe injury required to induce AKI in patients with DM relative to patients without DM (Table 4).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have hypothesized that diabetic patients who develop AKI may possibly have reduced nephron mass and perhaps less severe associated nonrenal disease compared to those without diabetes, suggesting that a more milder form of in-jury was required to cause AKI in this group of patients [18]. Besides, in support of our findings, previous study has documented that diabetic patients have predominantly stage 1 AKI with fast recovery [28]. We therefore suspect the lower risk of in-hospital and post-hospitalization mortality associated with DM may be due to a lower severity of cardiovascular disease in the surviving population together with a less severe injury required to induce AKI in patients with DM relative to patients without DM (Table 4).…”
Section: Discussionsupporting
confidence: 89%
“…Relaxing eligibility criteria related to comorbidity and age are critical for minority populations because they are more likely to have other chronic illnesses and may be more susceptible at earlier ages (Mathioudakis et al, 2016; Prasad, Helder, Brown, & Schaff, 2016; Yoo, De, Wilkins, Smith, & Blumenthal, 2016). We also provided small site grants each year to assist with retention items, parking and refreshments.…”
Section: Resultsmentioning
confidence: 99%
“…Whether black race is a risk factor for non-COVID-19-associated AKI has not been clearly established as data are inconsistent. 24,[46][47][48][49] Several studies failed to find any relationship between race and the development of AKI. 46,47 In contrast, a meta-analysis of .1.3 million individuals performed by the CKD Prognosis Consortium found that black patients had a higher risk of AKI than white patients at higher levels of eGFR and at most urinary albumin-creatinine ratios.…”
Section: Discussionmentioning
confidence: 99%